Decolonial Epistemology and Information Science: an analysis of ENANCIB Annals - Bamberg, Callu Ribeiro Ferreira Pedreira e Andrade; Vital, Luciane Paula; Costa, Amábile; Garcez, Dirnele Carneiro (InCID: Revista de Ciência da Informação e Documentação, 2022)
This study seeks to reflect on the dialogue between decolonial epistemology and Information Science (IC). It aims to identify scientific papers on decolonial epistemology in the Annals of the National Meeting of Research on Information Science. A survey of its scientific production, available online, was carried out between 2010 and 2019, finding that 3,408 scientific studies used content analysis. We chose 42 on ethno-racial, gender, otherness, and racism issues to be read in full. We found that most communications were based on other theoretical conceptions outside the scope of this study. As a result, we show two IC articles on decolonial epistemology. This reflects a need to discuss decolonial epistemology in IC given its importance and multiple possibilities.